IDENTIFIKASI PENILAIAN KINERJA KEUANGAN DAN KESEHATAN BANK PERKREDITAN RAKYAT (BPR) DI SURABAYA BERDASARKAN NERACA TRIWULAN DESEMBER 2010 DAN DESEMBER 2011 - KUSUMA DEVI, FITRIYAH Kusuma (Jurnal Akuntansi AKUNESA, 2013)
The purpose of this paper is to assess the performance of BPR in Surabaya in the periodDecember 2010 and December 2011 was assessed through financial ratios represented bythe Reserve Requirement (RR), ROA, and DER. RR which in general has increased, as seenfrom the Rural "A" is an increase of 0.9%, "B" 0.06%, "C" 0.16%, "E" of 0.25%, "H" 9.33%,return on assets ratio has increased BPR in Surabaya from December 2010 to December2011. The increase in ROA is represented BPR BPR "A" of 2.38%, "B" 0.32%, "C" 0.05%,"G" 0.28%, "H" 1.76%. The increase in the value of ROA shows that BPR had improvedperformance compared to the past. In general assessment of the ratio of DER in December2011 has increased compared to December 2010 the percentage value that can be seen fromRural "A" 23.78%, "B" 54.71%, "E" 277.43% "H" of 56, 17%. Rural health in general inSurabaya is in good healthy condition in December 2010 or December 2011Keywords: BPR, Financial Ratios, Camel